The Beginnings of Lottery Game in Colombia: Among Luck, Social Control and Public Benefit (2017)
Summary: This article investigates the operation of lottery game in Colombia since the end of the Hispanic domain period, the process of Independence and the first years of republican life. The methodology involves a descriptive and qualitative study based on consultation of primary sources of that time. It is noticed that in the old Spanish regime and the Republican lottery system was in charge of official agencies who made this system, not a philanthropic matter as they had originally proposed, but a process to cover the few state coffers.